Ursane-type nortriterpenes with a five-membered A-ring from Rubus innominatus. (August 2015) - Chen, Zhenzhong; Tong, Ling; Feng, Yuanli; Wu, Jizhou; Zhao, Xiaoya; Ruan, Hanli; Pi, Huifang; Zhang, Peng
Graphical abstract: Two five-membered A-ring nortriterpenes (1 and2 ) and six triterpenes (3 –8 ) along with 17 known triterpenes were isolated from the roots of Rubus innominatus . Highlights: Separation and identification of 8 triterpenes from the roots of Rubus innominatus . Two of the compounds have a distinctive contracted five-membered A-ring norursane-type skeleton. Four compounds exhibited strong inhibitory effect on TNF- α, IL-1 β, and IL-6 production in LPS-induced RAW 264.7 macrophages. Abstract: Two nortriterpenes (rubuminatus A and B), which contain a distinctive contracted a five-membered A-ring ursane-type skeleton, and six triterpenes along with 17 known triterpenes were isolated from the roots of Rubus innominatus S. Moore. These structures were determined to be 19 α -hydroxy-2-oxo-nor- A(3)-urs-12-en-28-oic acid, 1 β, 19 α -dihydroxy-2-oxo-nor-A(3)-urs-12-en-28-oic acid, 1 β, 2 α, 3 α, 19 α -tetrahy droxyurs-12-en-23-formyl-28-oic acid, 1 β, 2 α, 3 α, 19 α, 23- pentahydroxyurs-11-en-28-oic acid, 1-oxo-siaresinolic acid, 2 α, 3 α -dihydroxyolean-11, 13(18)-dien-19 β, 28-olide, 1 β, 2 α, 3 α -trihydroxy-19-oxo- 18, 19-seco-urs-11, 13(18)-dien-28-oic acid, and 2-O-benzoyl alphitolic acid based on extensive spectroscopic analyses. In vitro anti-inflammatory abilities to modulate the production of TNF- α, IL-1 β, and IL-6 in LPS-induced RAW 264.7 macrophages of the compounds were determined. Rubuminatus A and B, as well as 1-oxo-siaresinolic acid and 2 α, 3 α -dihydroxyolean-11, 13(18)-dien-19 β, 28-olide, exhibited significant inhibitory effects on these cytokines.